Price Integration Analysis of Crude Oil and Vegetable Oils - Resti Prastika Destiarni; Ahmad Syariful Jamil (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2021)
The importance of palm oil as Indonesia's main export commodity from the non-oil and gas sector makes a study about the price integration of crude oil and vegetable oils is conducted. The time-series data is usedÂ are monthly data from 2002:2 to 2019:4. Using the Vector Correction Model (VECM), this study aimed to analyze the price integration among Log of Crude Oil Price (LCOP), Palm Oil Price (LPOP), Soybean Oil Price (LSOP), Sun Flower Oil Price (LSFOP) and Rapeseed Oil Price (LROP). Augmented-Dickey Fuller (ADF) stationary test results show that the time series for those data are stationary at first difference. Using the Pearson Correlation test among price data indicates that there is a high positive correlation among those price data. It reveals a high degree of short-run integration among oil price data. Based on the Johansen cointegration test, the result reveals the presence of long-run relationships among determinants. Knowing presence of cointegration among the data, a bivariate cointegration test was conducted in this study. The test showed that LCOP did not have long-run relationship with vegetable oil prices. The Engel Granger Causality test revealed that generally, LPOP have influence on the movement both LCOP and other vegetable oil prices.